Chromosomal assignment of two endogenous ecotropic murine leukemia virus proviruses of the AKR/J mouse strain. - Taylor, B A (1985)
The AKR/J mouse strain is genetically fixed for three different ecotropic murine leukemia virus genomes, designated Akv-1, Akv-3, and Akv-4 (Emv-11, Emv-13, and Emv-14). With recombinant inbred strains and crosses with linkage-testing stocks, Akv-3 and Akv-4 were placed on the mouse chromosome map. Akv-3, which encodes a replication-defective provirus, maps near the agouti coat color locus, a, on chromosome 2. Akv-4, which is replication competent, maps near the neurological mutant gene locus trembler, Tr, on chromosome 11. Akv-1 and Akv-2 (Emv-12), an ecotropic provirus carried by AKR/N but not AKR/J, have previously been mapped to chromosome 7 and 16, respectively. Thus, the four Akv proviruses mapped to date are on four different chromosomes. Akv-3 is the second ecotropic murine leukemia virus provirus to be mapped near the agouti locus. The results are discussed in relation to possible nonrandomness of viral integration.